Imperialism in the novels of Aphra Behn, Jane Austen and Jean Rhys: a reading of Oroonoko, Mansfield Park and Wide Sargasso Sea - Sharmin, Farheena (BRAC University, 2017)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in English, 2013.